1997
DOI: 10.1093/jmedent/34.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of Ixodes pacificus (Acari: Ixodidae) Using Allozymes

Abstract: Genetic analysis of the population structure of the western blacklegged tick, Ixodes pacificus Cooley & Kohls, was conducted using allozymes. This vector tick transmits the Lyme disease spirochete, Borrelia burgdorferi Johnson, Schmid, Hyde, Steigerwalt & Brenner, in the far-western United States. It ranges from British Columbia to Baja California and disjunct populations are present in Oregon, Nevada, Utah, and Arizona. Host-seeking adult ticks were collected from vegetation across the range of the species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…pacificus is responsible for the transmission of B. burgdorferi in the western US. Low to moderate gene flow has been observed in this tick vector using eight polymorphic allozymes against 20 populations sampled along the species range (Kain et al, 1997). A possible differentiation between northern and southern regions was particularly strong at one locus.…”
Section: Ixodesmentioning
confidence: 96%
See 1 more Smart Citation
“…pacificus is responsible for the transmission of B. burgdorferi in the western US. Low to moderate gene flow has been observed in this tick vector using eight polymorphic allozymes against 20 populations sampled along the species range (Kain et al, 1997). A possible differentiation between northern and southern regions was particularly strong at one locus.…”
Section: Ixodesmentioning
confidence: 96%
“…Two major mitochondrial lineages, possibly from mtDNA introgression from D. nitens; microsatellites predict three recently diverged genetic groups in Alberta Crosbie et al (1998), Leo et al (2010Leo et al ( , 2012Leo et al ( , 2014 Dermacentor andersoni Variable structure depending on scale and markers used; high structure observed among host-specific races; also sex-biased dispersal is known Casati et al (2008), De Meeûs et al (2002, Delaye et al (1997Delaye et al ( , 1998, Dinnis et al (2014), Healy (1979a,b), Kempf et al (2009b), Noureddine et al (2011 Ixodes pacificus DNA sequence (COIII), allozymes High structure on highly mobile hosts Kain et al (1997Kain et al ( , 1999, McLain et al (1995), Wesson et al (1993) Ixodes scapularis Microsatellites, DNA sequence (16S/cytc) High structure on highly mobile hosts Humphrey et al (2010), Kempf et al (2009bKempf et al ( , 2010Kempf et al ( , 2011, Krakowetz et al (2011), McLain et al (1995, Norris et al (1996), Qiu et al (2002), Rich et al (1995), Wesson et al (1993) …”
Section: Dermacentor Albipictusmentioning
confidence: 99%
“…Although the populations of I. pacificus are principally coastal, isolated inland populations have been described in such arid overall climates as Mohave County, Arizona (Olson et al 1992) and the southwestern corner of Utah (Kain et al 1997). There is no evidence of genetic isolation among these diverse populations of I. pacificus (Kain et al 1999).…”
Section: L I N I C a L A S P E C T S D I A G N O S I S A N D T R Ementioning
confidence: 99%
“…However, the ITS-2 region is not useful for assessing phylogenetic relationships among ticks because the region is variable and ticks evolved relatively recently (Rich et al 1997). Other genetic studies using allozymes for I. pacificus Cooley (Kain et al 1997) and I. ricinus (L.) (de Laye et al 1997) found a lack of differentiation among the populations between nearby localities and high rates of gene flow, indicating a rapid expansion of each population. Those allozyme studies concluded that the dispersal and population size of the host as well as use by ticks of a broad host range contributes to the great amounts of gene flow.…”
Section: Introductionmentioning
confidence: 99%